Optimal Sharing Strategies in Dynamic Games of Research and Development - Nisvan Erkal; Deborah Minehart (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
This paper builds a theoretical foundation for the dynamics of knowledge sharing in private industry. In practice, research and development projects can take years or even decades to complete. We model an uncertain research process, where research projects consist of multiple sequential steps. We ask how the incentives to license intermediate steps to rivals change over time as the research project approaches maturity and the uncertainty that the firms face decreases. Such a dynamic approach allows us to analyze the interaction between how close the firms are to product market competition and how intense that competition is. If product market competition is relatively moderate, the lagging firm is expected never to drop out and the incentives to share intermediate research outcomes decreases monotonically with progress. However, if product market competition is relatively intense, the incentives to share may increase with progress. These results illustrate under what circumstances it is necessary to have policies aimed at encouraging cooperation in R&D and when such policies should be directed towards early vs. later stage research.
Keywords: D81; L24; O31; O32; 330; Multi-stage R&D; Innovation; Knowledge Sharing; Licensing; Dynamic Games